1977
DOI: 10.1111/j.1471-0528.1977.tb12480.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and the Acute Porphyrias

Abstract: An analysis is presented of the obstetric histories of 50 women with acute porphyria, comprising 39 with acute intermittent porphyria, 3 with variegate porphyria and 8 with hereditary coproporphyria. Fifty-four per cent of the women with acute intermittent porphyria had an acute attack of porphyria in pregnancy and/or the puerperium. Only one maternal death was recorded. One patient with variegate porphyria and two with hereditary coproporphyria had an attack related to pregnancy. The total fetal wastage was 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…Neilson, et al [4] reported that maternal mortality was 42.5% due to attacks of porphyria during pregnancy. Brodie, et al [5] showed that 54% (27/50) of women with acute porphyria had an acute attack during pregnancy and that the babies born were significantly smaller than those who did not have a porphyria crisis. Andersson, et al [6] demonstrated that miscarriage was more common amongst women with manifest AIP.…”
Section: Discussionmentioning
confidence: 99%
“…Neilson, et al [4] reported that maternal mortality was 42.5% due to attacks of porphyria during pregnancy. Brodie, et al [5] showed that 54% (27/50) of women with acute porphyria had an acute attack during pregnancy and that the babies born were significantly smaller than those who did not have a porphyria crisis. Andersson, et al [6] demonstrated that miscarriage was more common amongst women with manifest AIP.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study of pregnancy outcome in patients with known porphyria, the attack rate is only 16% in the antenatal period and 8% in puerperium. 12 We believe tllat the initial porphyria attack, which took the form of a generalized seizure and hypertension in our patient, occurred after cesarean delivery and probably was related to reduced caloric intake after surgery and pyelonephritis. The use of phenytoin and nifedipine to conn'ol her seizure and hypertension further aggravated the metabolic derangement, resulting in progressive motor neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…A survey by Brodie et al [2] stated that 54% of women with the disease who become pregnant had an acute attack during pregnancy or the puerperium. Our patient had suffered acute abdominal attacks in her last pregnancy and even neurological dysfunction in the form of seizures and was unwilling to take risk of continuing pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Given a 54-95% increased risk of acute episodes in pregnancy, the couple opted for a pregnancy termination [2] . Anaesthetist opinion was taken regarding anaesthesia and drugs to be avoided, as a large number of drugs can precipitate an acute attack.…”
Section: Acute Intermittent Porphyria In Pregnancymentioning
confidence: 99%